Policy goals for improved water quality in the Baltic Sea : when do the benefits outweigh the costs? - Hyytiäinen, Kari; Ahlvik, Lassi; Ahtiainen, Heini; Artell, Janne; Huhtala, Anni; Dahlbo, Kim (Springer, 2015)
This paper develops and applies a spatially explicit bioeconomic model to study transboundary nutrient pollution of the Baltic Sea. We combine catchment, marine and economic models covering the entire Baltic Sea region to weigh the costs of nutrient abatement and the benefits of improved water quality and solve for the optimal level of water protection. The overall benefits of the Baltic Sea Action Plan, the present convention on nutrient abatement, clearly outweigh the costs. Nevertheless, the total cost could be almost halved if the mix of measures and the regional targets were planned in a spatially cost–effective manner and if the consequent reductions of nitrogen and phosphorus, the two nutrients causing eutrophication, were better balanced. Policy optimizations, however, suggest that the optimal level of nutrient abatement is somewhat lower than the more ambitious level envisaged by the convention. The welfare gains from cost sharing that makes the optimal level of nutrient abatement worthwhile for all littoral countries would be 170 million euros annually
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; cost-effectiveness; environmental valuation; nitrogen; optimization; phosphorus; Itämeri; fosfori; typpi; phosphorus; nitrogen; rehevöityminen; ympäristö; arvottaminen; kustannus-hyötyanalyysi